Cultural Signs in Multilingual Drama Feature Films: Rendition Strategies - Homa Tavousi; Azadeh Eriss (Media and Intercultural Communication: A Multidisciplinary Journal)
The contemporary international landscape is more accurately portrayed in the works of filmmakers who increasingly choose to incorporate multiple languages. However, this diversity introduces additional challenges during the translation process. This research describes the translation strategies employed in dubbing multilingual films and explore the differences in translating third language (L3) in Iranian national and private channels based on the models of Zabalbeascoa and Voellmer (2014) and Sanz Ortega (2011). Three films were selected which were dubbed and broadcast by two national TV studios: the Islamic Republic of Iran Broadcasting Company (IRIB) and an online Video on Demand (VOD) service, Filimo. The analysis revealed that the most prevalent verbal technique was neutralization (Ai), which reduced linguistic variety. Non-verbal signs were adapted to adhere to the sociocultural norms of Iranian culture. Filimo, in its dubbing efforts, maintains films closer to their original duration compared to IRIB. Filimo’s commitment to preserving more scenes from the original film without compromising the plot exceeds that of IRIB, providing audiences with a more enriched viewing experience.